2004
DOI: 10.1074/jbc.m310526200
|View full text |Cite
|
Sign up to set email alerts
|

p38MAPK Acts in the BMP7-dependent Stimulatory Pathway during Epithelial Cell Morphogenesis and Is Regulated by Smad1

Abstract: inhibitor, blocked the stimulatory effect of BMP7 on mIMCD-3 cell morphogenesis but had no effect on BMP7-dependent inhibition in a three-dimensional culture model. To identify mechanisms by which BMP7-dependent inhibitory signaling suppresses p38 MAPK activity, we measured p38 MAPK activity in ligand independent mIMCD-3 models of enhanced and suppressed Smad signaling. Basal activity of p38 MAPK was decreased in mIMCD-3 cells and in embryonic kidney tissue expressing a constitutively active activin-like kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 37 publications
3
55
1
Order By: Relevance
“…30 Immunohistochemistry demonstrated wide distribution of phosphorylated p38 MAPK (phospho-p38 MAPK)-positive cells throughout the control kidneys ( Figure 9A); however, in BMP7 CKO kidneys, we observed decreased staining specifically in proximal tubules ( Figure 9, B and D). Western blot analysis of tissue from isolated cortex demonstrated marked decrease of phospho-p38 MAPK in BMP7 CKO kidneys ( Figure 9E), consistent with the immunohistochemistry ( Figure 9, B and D, compare with C and E).…”
Section: Phosphorylated P38 Mapk Localizationmentioning
confidence: 85%
“…30 Immunohistochemistry demonstrated wide distribution of phosphorylated p38 MAPK (phospho-p38 MAPK)-positive cells throughout the control kidneys ( Figure 9A); however, in BMP7 CKO kidneys, we observed decreased staining specifically in proximal tubules ( Figure 9, B and D). Western blot analysis of tissue from isolated cortex demonstrated marked decrease of phospho-p38 MAPK in BMP7 CKO kidneys ( Figure 9E), consistent with the immunohistochemistry ( Figure 9, B and D, compare with C and E).…”
Section: Phosphorylated P38 Mapk Localizationmentioning
confidence: 85%
“…[12][13][14] During the process of kidney development, Bmp7 prevents metanephric mesenchymal cells from undergoing apoptosis, 12,15 promotes metanephric differentiation, 16 and controls the proliferation and apoptosis of epithelial cells in the collecting tubules. 17 In a previous study, we demonstrated that Trps1 is regulated by growth and differentiation factor 5 (Gdf5), another BMP that shares the same receptor with Bmp7, in ATDC5 chondrogenic cells. 18 This finding immediately raised the possibility that Trps1 may also act downstream of Bmp7 on metanephric mesenchymal cells during early kidney development.…”
mentioning
confidence: 97%
“…1997, 2001; Hu et al. 2004). In the ureteric bud, which differentiates into the collecting duct, a concentration gradient of BMP7 is considered to exist with higher concentration at the tip and lower level in the trunk.…”
Section: Discussionmentioning
confidence: 99%
“…1997; Hu et al. 2004). In murine inner medullary collecting duct (mIMCD) cells, BMP7 stimulated p38 but not ERK or JNK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation